2005
DOI: 10.1111/j.1365-313x.2005.02333.x
|View full text |Cite
|
Sign up to set email alerts
|

Cap‐independent translation of maize Hsp101

Abstract: SummaryMaize embryonic axes contain stored mRNAs, some of which are able to undergo cap-independent translation initiation during germination. The Hsp101 mRNA, encoding a heat shock protein, is essential for thermotolerance induction and is present among the stored transcripts. This research aimed to investigate whether the Hsp101 transcript is IRES-driven regulated upon heat stress. Hsp101 transcribed either in vitro or in vivo was efficiently translated via a cap-independent mechanism. This was observed eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 49 publications
4
56
0
Order By: Relevance
“…IRES-mediated regulation of translation has been described in eukaryotic cellular mRNAs that are active during mitosis or under stress conditions when cap-dependent translation is inhibited (Pyronnet et al, 2000;Gilbert et al, 2007;Sonenberg and Hinnebusch, 2007), thereby providing a mechanism for continued synthesis of specific proteins when global translation is prevented. Consistent with this, the first IRES identified in plant cells was in mRNA encoding the maize (Zea mays) heat shock protein, Hsp101, and this accounts for its cap-independent translation during heat stress (Dinkova et al, 2005). FCA functions to regulate flowering time by repressing FLC, but we also know it plays other roles in regulating the expression of genome sequences that are also targets of RNA-mediated chromatin silencing and likely acts somewhat redundantly with other autonomous pathway components to regulate a wider set of gene targets (Veley and Michaels, 2008).…”
Section: Discussionsupporting
confidence: 49%
“…IRES-mediated regulation of translation has been described in eukaryotic cellular mRNAs that are active during mitosis or under stress conditions when cap-dependent translation is inhibited (Pyronnet et al, 2000;Gilbert et al, 2007;Sonenberg and Hinnebusch, 2007), thereby providing a mechanism for continued synthesis of specific proteins when global translation is prevented. Consistent with this, the first IRES identified in plant cells was in mRNA encoding the maize (Zea mays) heat shock protein, Hsp101, and this accounts for its cap-independent translation during heat stress (Dinkova et al, 2005). FCA functions to regulate flowering time by repressing FLC, but we also know it plays other roles in regulating the expression of genome sequences that are also targets of RNA-mediated chromatin silencing and likely acts somewhat redundantly with other autonomous pathway components to regulate a wider set of gene targets (Veley and Michaels, 2008).…”
Section: Discussionsupporting
confidence: 49%
“…Because two different mRNA pools exist in germinating seeds, the stored mRNAs, and the de novo-synthesized mRNAs (4,40), it is possible that these different initiation systems allow their respective recruitment during germination. Consistent with this, maize embryonic axes were shown to contain stored mRNAs, some of which are efficiently translated via a cap-independent mechanism during germination (41).…”
Section: Sugarbeet Seeds Use Distinct Mechanisms For Translation Initsupporting
confidence: 52%
“…For example, an internal ribosome entry site (IRES) in the mRNA allows the ribosome to directly associate with a sequence within the mRNA. Several plant viral RNAs are translated through IRES sequences (Jaag et al, 2003;Dorokhov et al, 2006;Karetnikov and Lehto, 2007), but so far only one cellular plant mRNA was shown to be translated through an IRES-dependent mechanism (Dinkova et al, 2005). Translation of bZIP11 does not depend on IRES as all sequences 3# of the uORF2 can be deleted without affecting translation of the main ORF ( Fig.…”
Section: Translation Of the Bzip11 Main Orfmentioning
confidence: 99%